AN INTEGRATION APPROACH TO REDERIVE THE GREEN AND AMPT WATER INFILTRATION EQUATION AND ITS EXPERIMENTAL EVALUATION - S. N. Abdel Al-Hassan; M. I. Aoda (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The approach of the Green and Ampt (1911) for describing water entry into unsaturated porous media was critically appraised .Theoritical revision was made of a previous mathematical approach, to give it complete rigor in describing water flow for rectangulary abrupt water content profile. Rigorous rederivation of this equation yielded a straightforward and complete interpretation of the suction head at the wet front tw. The suction head tw at the wet front is given as the integral of the suction-head- t dependent hydraulic conductivity function K (t) with the upper limit of the integral being the suction head t0 at the initial water content q0. Furthermore, tw is shown to be a constant of the flow process even when G-A rectangular abruptness does not hold. The equation is shown to be the hydraulic conductivity K (q1) of the wet region behind the wet front which is a function of the constant averaged water content of the wet region. For experimental data of cumulative infiltration with time, both the G-A and two –term Philip equation were fitted by nonlinear regression. The G-A equation gave better fitting than Philip equation for certain soil texture, but both equations gave a very well fitting (%1error). G-A parameter K1 gave a very good agreement with the measure hydraulic conductivity for all soil studied. The other parameter tw was calculated from the fitted parameter a and show values correlated to soil texture in expected .Abruptnen of soil water transient profile was tested using soil moisture probes-GS3.